Trikafta Rescues F508del‐CFTR by Tightening Specific Phosphorylation‐Dependent Interdomain Interactions - Guangyu Wang (Natural Sciences)
ABSTRACT Trikafta effectively corrects the thermal and gating defects associated with the F508del mutation, the most common cause of cystic fibrosis (CF), even at physiological temperatures. However, the exact correction pathway is still unclear. Here, noncovalent interactions among two transmembrane domains (transmembrane domain 1 [TMD1] and transmembrane domain 2 [TMD2]), the regulatory (R) domain, and two nucleotide binding domains (nucleotide binding domain 1 [NBD1] and nucleotide binding domain 2 [NBD2]) were analyzed. The thermal stability of NBD1 was also evaluated through its tertiary constrained noncovalent interaction networks, or thermoring structures. The results demonstrated that Trikafta binding to flexible TMD1 and TMD2 rearranged their interactions with the R domain upon phosphorylation, coupling tightened cytoplasmic TMD1–TMD2 interactions to tightened Mg/ATP‐dependent NBD1–NBD2 dimerization, which stabilized NBD1 above human body temperature. In essence, although the F508 deletion primarily causes a thermal defect in NBD1, leading to a gating defect at the TMD1–TMD2 interface, Trikafta allosterically reverses these effects. These mechanistic insights into the precise correction pathway of this misfolded channel facilitate optimizing CF treatment.